2023
DOI: 10.1186/s12889-023-16184-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of health behaviors and mental health on students’ academic achievement: a cross-sectional study on lebanese university students

Dalal Hammoudi Halat,
Souheil Hallit,
Samar Younes
et al.

Abstract: Background High academic achievement, an important determinant of future success, is known to be influenced by many factors including dietary behavior, lifestyle and mental health, among others. The objectives of the current study were to explore university students’ nutritive habits, daily lifestyle, and mental status, and to scrutinize the associations between these factors and students’ academic achievement. Methods A cross-sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 114 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…About 71% of the LAA cohort expressed dissatisfaction with their mental health, 72% expressed dissatisfaction with their physical health, and 67% expressed dissatisfaction with their academic achievement, while 98% of HAA students expressed satisfaction with their academic achievement, 54% expressed satisfaction with their physical health, and 74% expressed satisfaction with their mental health. Although it was not assessed in this study, previous research has found that students that reported more psychological distress and increased frequency of eating out was significantly associated with lower subjective academic achievement scores; illustrating the interplay between diet, lifestyle satisfaction, and academic achievement [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 71% of the LAA cohort expressed dissatisfaction with their mental health, 72% expressed dissatisfaction with their physical health, and 67% expressed dissatisfaction with their academic achievement, while 98% of HAA students expressed satisfaction with their academic achievement, 54% expressed satisfaction with their physical health, and 74% expressed satisfaction with their mental health. Although it was not assessed in this study, previous research has found that students that reported more psychological distress and increased frequency of eating out was significantly associated with lower subjective academic achievement scores; illustrating the interplay between diet, lifestyle satisfaction, and academic achievement [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As international research studies show, university students need support for adequate physical activities and maintaining a healthy lifestyle as it all has a direct impact on health condition (Henshaw& Archibald, 2013;Tafireyi & Grace, 2022), self-efficacy (Zhang & Zhang, 2022), and quality of life of students (Abrantes, et al, 2022). In addition, studies indicate that there is a positive correlation between students' physical fitness and academic achievements (Elmagd et al, 2015;Kljajević, et al, 2021;Redondo-Flórez, Ramos-Campo & Clemente-Suárez, 2022;Gejalakshmi & Swaminathan, 2022, Hammoudi, Halat, 2023.…”
Section: Introductionmentioning
confidence: 99%